Pengaruh Kecerdasan Buatan Penerjemahan Teks-Teks Agama Islam: Tinjauan Literatur tentang Algoritma dan Mesin Penerjemahan - Fitryansyah, Muhammad Andryan; Fauziah, Fatimah Nur (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2024)
Artificial intelligence (AI) is transforming diverse fields, including the interpretation of Islamic religious texts. This study examines the influence of AI, particularly in the context of Nusantara Islamic traditions, and evaluates its ethical and theological implications. The research addresses the growing need to understand how AI intersects with traditional Islamic scholarship in Southeast Asia, emphasizing Indonesia as a case study. Using a qualitative literature review method, the study analyzes peer-reviewed articles, books, and reports from the last ten years that focus on AI applications in interpreting Islamic religious texts. Key findings reveal that AI significantly enhances accessibility and efficiency in interpreting religious texts by offering tools for translation, pattern recognition, and thematic analysis. However, AI faces notable limitations, including contextual inaccuracies and an inability to grasp the nuanced meanings of religious doctrines deeply rooted in cultural and historical traditions. The ethical and theological concerns identified include questions of interpretative authority, the risk of textual distortion, and the moral responsibilities of AI developers. The research highlights the need for collaborative frameworks between technologists and religious scholars to ensure ethically sound and theologically informed AI applications. It contributes to the literature by focusing on Nusantara Islamic texts and proposing actionable guidelines for integrating AI in religious studies responsibly. This study provides a foundation for further interdisciplinary research to balance technological innovation with the preservation of Islamic interpretive traditions.